Ground temperature monitoring for a coaxial geothermal heat exchangers field: practical aspects and main issues from the first year of measurements. (Rudarsko-geološko-naftni zbornik, 2018)
Ground temperature at shallow depth (< 50 m) is not stable, nor in space, neither in time, and its behaviour is the result of superimposition of effects of heat pulses of different origin: solar, geothermal and anthropic. The correct assessment of ground temperature is a crucial point when designing a shallow geothermal energy system. In geothermal closed loop projects, more the borehole heat exchangers are short, more the contribution of the ground temperature variability on the heat exchange is prominent. Monitoring ground temperature can be very useful to correctly understand the behaviour of a shallow geothermal reservoir subjected to heat extraction and/or injection by a ground source heat pump system. The present work illustrates the practical aspects and main issues occurred in the installation, testing and working phases of a monitoring system realised to record ground temperature in a geothermal application. The case study is a field of eight coaxial borehole heat exchangers, 30 m long, connected to a novel prototype of dual source (air and ground) heat pump.